Maternal Health Literacy and Antenatal Care Program in Coastal Indonesia : A review - Siti Nurfadilah H; Waode Sitti Nurrokhmadani; Aswanty (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: In 2017, approximately 295.000 women died due to complications during pregnancy and childbirth, despite a 38% decline in the global maternal mortality rate since 2000. One contributing factor to maternal mortality in Indonesia is the persistently low level of health literacy among women. Moreover, Indonesia has not yet fully adopted the antenatal care (ANC) guidelines recommended by the World Health Organization (WHO), which are essential for ensuring quality maternal care and reducing the risks of maternal mortality and high-risk pregnancies. While previous studies have explored ANC in urban and rural settings, there remains a lack of research focusing on coastal and island communities, which often present unique characteristics and distinct health challenges. Objective: This study aims to analyze the level of health literacy among pregnant women and their utilization of antenatal care services in coastal areas. Method: A systematic literature review was conducted by searching five major databases: PubMed, Elsevier, Google Scholar, Open Access, and nationally accredited journals. The inclusion criteria were: 1) studies involving women in the prenatal period, 2) articles written in English, and 3) clear descriptions of maternal health service utilization. Thematic synthesis was applied in three stages: 1) coding of relevant text, 2) development of descriptive themes, and 3) generation of analytical themes. Results: From an initial pool of 1.336 articles, forty-four studies were included in the final analysis. The majority of these studies were conducted in the United States, with additional studies from Indonesia, Europe, and Africa. The synthesis revealed four key themes: 1) socioeconomic status and its determinants, 2) functional health literacy, 3) interactive health literacy, and 4) critical health literacy. Conclusion: The findings highlight that multiple dimensions of health literacy significantly influence the use of antenatal care services. Despite varying levels of knowledge about maternal health, limited access, socioeconomic barriers, and insufficient engagement with healthcare providers remain major obstacles in coastal communities. A tailored approach that strengthens all levels of health literacy and improves healthcare infrastructure is essential to enhance ANC utilization in these areas. Keywords: Health literacy, antenatal care, pregnant women, coastal areas., Indonesia